Optimalisasi Penguasaan Mufradāt Bahasa Arab Melalui Voice Method dan Drill pada Siswa Madrasah Tsanawiyyah Dar al-Taqwā 1 Pasuruan - Junaihil, Junaihil; Syaifullah, Syaifullah; Hasyim, Mochamad (STAI Ali bin Abi Thalib Surabaya, 2025)
This study aims to examine the effectiveness of applying the voice method and drill in improving students’ mastery of Arabic vocabulary. The research employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest model. Data were collected through a pretest, treatment, and posttest. The background of this study is based on the importance of creating a pleasant, interactive, and non-monotonous learning atmosphere so that students are more motivated to participate actively and are better able to comprehend the material. In practice, many madrasah tsanawiyah students face difficulties in mastering vocabulary due to limited prior knowledge, low self-confidence, and conventional teaching methods that tend to be less engaging. The findings revealed a significant improvement in vocabulary mastery following the application of the voice method and drill. Students’ average scores increased by 38.94 points, from 43.24 on the pretest to 79.12 on the posttest. The t-test yielded a t-value of 15.17, exceeding the t-table value of 2.120, indicating a significant difference between pretest and posttest results. The novelty of this study lies in integrating the voice method with drill exercises in the context of Arabic vocabulary learning at the madrasah tsanawiyah level. While previous studies emphasized each method separately, this research introduces a combined approach that has rarely been explored. The findings demonstrate that the collaboration of the voice method and drill not only significantly enhances vocabulary mastery but also contributes to increased learning motivation, creates a more enjoyable classroom environment, and challenges the perception of Arabic learning as rigid and monotonous.